2021
DOI: 10.1186/s12963-020-00227-y
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy intention data completeness, quality and utility in population-based surveys: EN-INDEPTH study

Abstract: Background An estimated 40% of pregnancies globally are unintended. Measurement of pregnancy intention in low- and middle-income countries relies heavily on surveys, notably Demographic and Health Surveys (DHS), yet few studies have evaluated survey questions. We examined questions for measuring pregnancy intention, which are already in the DHS, and additional questions and investigated associations with maternity care utilisation and adverse pregnancy outcomes. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
0
13
1
Order By: Relevance
“…The cost of delayed pregnancy awareness is great: adoption of appropriate pregnancy habits is delayed [ 4 , 5 ] in the earliest, most fragile developmental window [ 6 9 ]. Moreover, unplanned pregnancy occurs at a rate of ~50% [ 10 13 ], and is associated with higher likelihood of adverse exposures [ 4 , 5 , 14 , 15 ], increased maternal morbidity and mortality [ 16 , 17 ], preterm birth and low childhood weight [ 18 21 ], elevated risk of birth defects [ 22 , 23 ], and poorer maternal psychological health [ 24 , 25 ]. As the effective window for emergency contraception is ~120 h at most [ 26 29 ], and as access to pregnancy testing and safe abortion access continues to be limited around the world [ 16 , 30 ], delayed confirmation poses considerable risks to pregnant individuals [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cost of delayed pregnancy awareness is great: adoption of appropriate pregnancy habits is delayed [ 4 , 5 ] in the earliest, most fragile developmental window [ 6 9 ]. Moreover, unplanned pregnancy occurs at a rate of ~50% [ 10 13 ], and is associated with higher likelihood of adverse exposures [ 4 , 5 , 14 , 15 ], increased maternal morbidity and mortality [ 16 , 17 ], preterm birth and low childhood weight [ 18 21 ], elevated risk of birth defects [ 22 , 23 ], and poorer maternal psychological health [ 24 , 25 ]. As the effective window for emergency contraception is ~120 h at most [ 26 29 ], and as access to pregnancy testing and safe abortion access continues to be limited around the world [ 16 , 30 ], delayed confirmation poses considerable risks to pregnant individuals [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may explain why large minorities of women with recent unwanted births report wanting more children in the future both in our data and across contexts. 15 Indeed, a recent study using NSFG data found teenagers to have the highest proportion of births categorized as unwanted, 32 and researchers using earlier rounds of the same study were puzzled as to why so many teenagers reported unwanted rather than mistimed births. 1,16 Researchers working in sub-Saharan Africa have expressed similar confusion.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Other research has revealed that many women who report a birth as unwanted (by indicating that a particular pregnancy came when they did not want more children; see Table 1) also report wanting more children in the future. 3,15,16 Still others have shown that desired fertility with a particular partner is closely related to pregnancy intentionality. 17,18 The United States (US) National Fertility Survey introduced the concept of a mistimed birth in 1965.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, a prospective understanding of pregnancy intention can inform who needs which kind of advice and can empower individuals or couples to formulate and achieve their reproductive intentions. 2 52 Such assessment allows the health care worker to provide contraception information or preconception care which may prevent unintended pregnancy, or enable people to optimize their health prior to pregnancy. 53 Several pilot studies regarding One Key Question have shown feasibility and acceptability and formal studies are underway to assess the impact of this tool on reproductive health.…”
Section: What Can We Do With the Information?mentioning
confidence: 99%